NEW MEDIA CHALLENGES: ANALYSIS OF FAMILY RELATIONSHIPS IN DESA NAMPES, PANDAAN, INDONESIA - Mahendra, Rafly Jibran; Aesthetika, Nur Maghfirah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Family involvement in developing children's academic and behavioral abilities is an important foundation in character formation. This study aims to analyze the role of the family, especially parents, in shaping adolescents' character through effective communication and moral education, as well as its impact when combined with the influence of new media. The method used was qualitative, with in-depth interviews with 30 adolescents and parents in Surabaya. The study results show that consistent parental guidance plays a significant role in strengthening family norms, although the challenges of the influence of digital media are increasing. The wise use of new media can be a tool to support character development if accompanied by active parental supervision. This study emphasizes the importance of collaboration between the role of family and technology to create a young generation with integrity.